Determining antecedents influencing beneficiaries income level from income generating programs / Norsuhada Sahedan - Sahedan, Norsuhada (2020)
The income generating program performance have become a significant research area since the introduction of productive welfare initiative in eradicating urban poverty just over a decade ago in Malaysia. Researchers have studied and proposed improvement to many factors such as entrepreneur traits as well as assistance facilities in order to investigate its effectiveness in eradicating poverty. The critical issue is whether entrepreneur traits and assistance facilities, do influence the level of income from income generating program. Thus, this research aims to investigate the relationships between assistance facilities which are training and in-kind transfer of business